Pengaruh Deterjen Terhadap Kualitas Air Permukaan - Gulo, Lestari Purnama Intan (Jurnal Perikanan dan Kelautan, 2025)
Population growth has increased the volume of household waste and has increased people's domestic activities as it is directly launched into waters. One of the major contributors to water pollution from domestic activities is the use of detergents, which contain chemical compounds such as surfactants and phosphates. Detergents contain active chemicals such as surfactants and phosphates which, while effective at removing dirt, can be bad for the environment. When these wastes enter rivers or lakes, they can damage the balance of aquatic ecosystems and disrupt the lives of living things in them. This article includes a review of the effects of active chemicals on surface water quality. A review of previous research shows that the presence of these wastes can reduce the physical, chemical and biological quality of water due to increased values of BOD, COD and nutrients such as phosphates and nitrates.